Single-frame measurement of the complete spatiotemporal field of ultrafast laser pulses using Carrier Frequency-Division Multiplexing Spectral Interferometry. (February 2023) - Li, Wei; Wang, Xiao; Hong, Yilin; Zeng, Xiaoming; Mu, Jie; Zuo, Yanlei; Li, Zhaoli; Su, Jingqin
Abstract: A single-frame complete spatiotemporal characteristics measurement method of ultrafast laser pulses, named Carrier Frequency Division Multiplexing Spectral Interferometry (CFDMSI), is proposed and demonstrated. Based on the idea of frequency division multiplexing, the 3D spatiotemporal field E ( x, y, t ) of a femtosecond laser pulse can be reconstructed from a single spectral interferogram. The implementation of CFDMSI is quite simple, just fixing a slit array at the entrance of an imaging spectrometer, then injecting the unknown pulse and the reference pulse into the imaging spectrometer at a certain cross angle. By recording and analyzing a single spectral interferogram, the unknown pulse's spatiotemporal field in the sampling area of the slit array can be obtained. The principle and implementation of CFDMSI are introduced, and its effectiveness is verified by a demonstration experiment. Highlights: A single-frame complete spatiotemporal characterization method is proposed. The Spectral Interferometry technique is improved by frequency division multiplexing. The spatiotemporal coupling of ultrafast lasers can be measured in real time.